Mechanical and Microstructural Properties of Geopolymer Concrete Containing Fly Ash and Sugarcane Bagasse Ash - Mohammed Ali M. Rihan; Richard O. Onchiri; Naftary Gathimba; Bernadette Sabuni (Civil Engineering Journal, 2024)
Portland cement plays a vital role in construction and building projects. However, its manufacturing process releases detrimental pollutants and contributes to climate change. The environmental concerns linked to the manufacturing of conventional Portland cement, such as its high energy demands, raw material consumption, and significant CO2 emissions, have prompted the need to look for alternatives such as geopolymer or green concrete. In addition, indiscriminate disposal of waste might have a detrimental effect on the environment. This paper investigates the mechanical and microstructural properties of geopolymer concrete incorporating fly ash and sugarcane bagasse ash as primary constituents. Sugarcane bagasse ash (SCBA) was employed as a partial substitute for Fly Ash (FA), with varying proportions ranging from 5% to 20% with increments of 5%. Alkaline activators utilized were NaOH (14M) and Na2SiO3, with a ratio of 1.5. Various tests, including the slump test, compressive strength test, splitting tensile strength test, and flexural strength test, were performed. The microstructural characteristics were assessed by scanning electron microscopy (SEM), energy dispersive analysis (EDS), and X-ray diffraction analysis (XRD). The results revealed that adding sugarcane bagasse ash influenced the workability of geopolymer concrete while enhancing its mechanical properties. The research findings have shown that the mixture comprising 5% SCBA has the greatest compressive strength of 64 MPa. Doi: 10.28991/CEJ-2024-010-04-018 Full Text: PDF